Experimental Study on the Shear Band of Methane Hydrate-Bearing Sediment - Xiaobing Lu (MDPI AG, 2021)
The occurrence of a shear band is often thought as the precursor of failure. To study the initiation of shear banding in gas hydrate-bearing sediments, two groups of triaxial compression tests combined with a CT (computer tomography) scan were conducted by triaxial CT-integrated equipment under two confining pressures and seven hydrate saturations. The macro stress–strain curves and the corresponding CT scanning images of the micro-structure and the distribution of the components were obtained. The geometric parameters of the shear bands were measured based on the CT images at four typical axial strains, respectively. The distribution characteristics of soil particles, water, hydrate and gas were also analyzed. It is shown that the existence of methane hydrate changes the mechanical property of hydrate-bearing sediment from plastic failure to brittle failure when the hydrate saturation is over 13%, which occurs in the range of the tests in this paper. The peak of the deviatoric stress increases with the hydrate saturation. The shear band is in either a single oblique line or inter-cross lines depending on the hydrate saturation, the effective confining pressure and the initial distribution of the gas hydrate. Most of the shear band surfaces are not straight, and the widths of the shear bands are almost non-uniformly distributed.